Cell surface proteomics identifies glucose transporter type 1 and prion protein as candidate biomarkers for colorectal adenoma-to-carcinoma progression. Issue 6 (2nd September 2011) - de Wit, Meike; Jimenez, Connie R; Carvalho, Beatriz; Belien, Jeroen A M; Delis-van Diemen, Pien M; Mongera, Sandra; Piersma, Sander R; Vikas, Maindad; Navani, Sanjay; Pontén, Fredrik; Meijer, Gerrit A; Fijneman, Remond J A
Abstract : Background and objective: Early detection of colon adenomas at high risk of progression and early-stage colorectal cancer (CRC) is an effective approach to reduce CRC death rates. Current screening methods lack specificity as they detect many adenomas that will never progress to CRC. The authors aimed to identify cell surface protein biomarkers with extracellular domains that could be targeted for molecular imaging and discriminate low-risk adenomas and normal colon from high-risk adenomas and CRC. Design: Cell surface proteins of five CRC cell lines were biotinylated, isolated and analysed by in-depth proteomics using gel electrophoresis and nanoliquid chromatography coupled to tandem mass spectrometry. Differential expression in adenomas and CRCs was based on mRNA expression and verified by immunohistochemical staining of tissue microarrays. Results: In total, 2609 proteins were identified in the cell surface fractions. Of these, 44 proteins were selected as promising cell surface candidate biomarkers for adenoma-to-carcinoma progression based on the following criteria: protein identification in at least four out of five cell lines, a predicted (trans)membrane location and increased mRNA expression in CRCs compared to adenomas. Increased protein expression in high-risk adenomas and CRCs compared to low-risk adenomas was confirmed by immunohistochemistry for glucose transporter type 1 (gene symbol SLC2A1 ; p<0.00001) and prion protein (gene symbol PRNP ; p<0.005). Conclusion: This study revealed glucose transporter type 1, prion protein and 42 other cell surface candidate biomarkers for adenoma-to-carcinoma progression that could potentially serve as targets for emerging molecular imaging modalities like optical imaging, 19 F-MRI and positron emission tomography.